Religious Rites of War beyond the Medieval West
1 online resource (832 pages)
Keywords: This is Volume Two of a two-volume collection that brings together contributions from cultural and military history to offer an examination of religious rites employed in connection with warfare as well as their transformative and power- and identity-building potential across political communities of medieval Northern, Central, and Eastern Europe. Covering the period ca. 900 and 1500, the work takes theoretical, textual and practical approaches to the research on religious warfare, and investigates the connections between, and significance and function of crucial war rituals such as pre-, intra- and postbellum rites, as well as various activities surrounding the military life of individuals, polities, and corporates. Contributors are Robert Antonín, Robert Bubczyk, Dariusz Dąbrowski, Jesse Harrington, Carsten Selch Jensen, Sini Kangas, Radosław Kotecki, Gregory Leighton, Kyle C. Lincoln, Jacek Maciejewski, Yulia Mikhailova, Max Naderer, László Veszprémy, and Dušan Zupka.